2009
DOI: 10.1007/s11596-009-0421-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-Aza-CdR on the proliferation of human breast cancer cell line MCF-7 and on the expression of Apaf-1 gene

Abstract: Hypermethylation in the promoter region of tumor suppressor genes is a common mechanism of gene silencing, which tends to occur in cancer. The effects of 5-Aza-2'-deoxycytidine (5-Aza-CdR), a specific DNA methyltransferase inhibitor, on the cell proliferation of human breast cancer cell line MCF-7 and on the expression of Apaf-1 gene were investigated. Human MCF-7 cells were incubated with increasing concentrations of 5-Aza-CdR for 12 to 120 h. The growth inhibition rates of MCF-7 cells were detected by MTT as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The data on APAF1 methylation in BC are presented in just one report of an in vitro study [12]. We have detected a high incidence of APAF1 gene hypermethylation (32%) in specimens of primary BC tumors, significantly higher than in specimens of normal tissue (0%).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The data on APAF1 methylation in BC are presented in just one report of an in vitro study [12]. We have detected a high incidence of APAF1 gene hypermethylation (32%) in specimens of primary BC tumors, significantly higher than in specimens of normal tissue (0%).…”
Section: Resultsmentioning
confidence: 71%
“…The data on hypermethylation of DAPK1 and APAF1 in some tumors have been presented, while studies of the contribution of methylation to regulation of these genes in BC are rare [9,12]. The relationship between suppression of APAF1 expression and methylation is demonstrated only in vitro on MCF-7 cells [12], and there are no reports about APAF1 methylation in clinical specimens of BC. A manifest increase of BCL2 expression in metastatic ovarian cancer is demonstrated [2].…”
mentioning
confidence: 99%
“…Xiong et al (32) examined the effects of 5-Aza-CdR on cell proliferation of human BC cell line MCF-7 and expression of APAF-1 gene. They observed that 5-Aza-CdR significantly suppressed the growth of MCF-7 cells and increased mRNA and protein expression of APAF-1 in MCF-7 cells; also, down-regulation of DNA methyltransferase 3b mRNA was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the ability of DAC to induce expression of tumor suppressor genes in a variety of cell lines. Tumor suppressor genes that are reported to increase their expression in response to DAC exposure include Rb , 38 p53 , 39 p21 , 40 p27 , p15 , 41 , 42 p16 , 29 , 43 , 44 Apaf-1 , 45 PTEN , BRCA1 , and BRCA2 . 46 , 47 In this study, the effect of DAC exposure on p15 , p16 , p53 , PTEN , BRCA1 , and BRCA2 expression was similar to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Treating MCF-7 cells with 0.5, 1, 2, and 5 µM DAC resulted in a 7%, 15%, 37%, and 45% decrease in proliferation, respectively. 45 Dai et al 64 used 102.4 µM DAC to decrease cell growth by 58.6%.…”
Section: Discussionmentioning
confidence: 99%